Recognition of the ICSID Awards in the USA - Ilia V. Rachkov (Московский журнал международного права, 2015)
This article deals with the current court practice of the US courts in connection with the recognition and enforcement of the decisions rendered by the international investment arbitration institutions, rendered in favor of the investor against any state (focusing on the ICSID arbitral awards). It also gives the up-to-date overview of the court practice (took place before 2015) with regard to such cases considered without notification of another party to a dispute (i.e. of the state). As the result of the research, the author concludes that at the moment the US court practice has two polar approaches, which leads to the following question: is it possible to apply the order for the recognition of the judgment of the other state so as to affirm the decision of the ICSID, where only one party is present? This question is also of importance for Russia as for the active party to different BITs.